Terrorism and Emergency Constitutions in the Muslim World - Christian Bjørnskov; Stefan Voigt (University of Hamburg, Institute of Law and Economics (ILE), 2019)
The Middle East is the most terror-prone region of the world. It is almost exclusively governed by autocratic regimes that often explicitly refer to Islam to justify some of their policies. In this paper, we analyse government reactions to terrorist events in the states that are members of the Organisation of Islamic Cooperation. We find that the respective emergency constitutions, despite the political characteristics of the region, do channel their behaviour. Emergency constitutions that make it relatively cheap for governments to declare a state of emergency are more likely to lead to such declarations. Our evidence thus suggests that emergency constitutions also impact on the behaviour of largely autocratic governments.
Keywords: K40; Z13; 330; terrorism; state of emergency; constitutional emergency provisions; institutions; positive constitutional economics; Middle East; Organization of Islamic Cooperation